2011
DOI: 10.1016/j.pneurobio.2011.01.002
|View full text |Cite
|
Sign up to set email alerts
|

The effect of pain on cognitive function: A review of clinical and preclinical research

Abstract: Cognitive impairment is commonly associated with the pain experience. This impairment represents a major obstacle to daily activities and rehabilitation, especially in the chronic pain population. Here we review clinical and preclinical studies that have investigated pain-related alterations in cognition. These include impaired attentional, executive and general cognitive functioning. We describe the anatomical, neurochemical and molecular substrates common to both cognitive processing and supraspinal pain pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

34
734
6
37

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 900 publications
(811 citation statements)
references
References 254 publications
34
734
6
37
Order By: Relevance
“…Because age (14), fatigue severity (42), and depressive symptoms (43) may significantly influence cognitive function as well as pain measurements, the analyses were also performed with these variables separately entered as additional predictor variables (covariates).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because age (14), fatigue severity (42), and depressive symptoms (43) may significantly influence cognitive function as well as pain measurements, the analyses were also performed with these variables separately entered as additional predictor variables (covariates).…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, we recently demonstrated that performance-based cognitive capabilities are significantly worse both in CFS patients with and without FM compared with healthy controls (13). Indeed, an overlap exists in components of the pain neuromatrix and brain regions involved in cognitive processing (e.g., anterior cingulate cortex, insular cortex, periaqueductal gray) (14). Together with the demonstrated changes in neuroplasticity [e.g., gray matter volume reduction (15)(16)(17)] and dysregultated neurochemistry [e.g., decreased levels of brain-derived neurotrophic factor (18), increased levels of gamma-aminobutric acid (19), increased levels of pro-inflammatory cytokines (20)], these pain-induced changes in resource utilization may (in part) explain (pain-related) cognitive impairment in chronic pain patients.…”
Section: Participants and Assessmentsmentioning
confidence: 98%
“…Third, a chronic pain population is 22 known to generally respond slower than pain-free participants. Indeed, general deficits in information processing have been frequently reported in patients with chronic pain [20,34]. This may have resulted in more noise in the reaction time data compared to studies in healthy volunteers.…”
Section: Discussionmentioning
confidence: 99%
“…It can trigger negative interference in daily activities and in the quality of life of the individuals, in addition to influencing cognitive aspects (7) . Pain is a stimulus capable of affecting the dynamic state of the encephalon, since the neural systems involved in cognition are also closely linked to modulation and perception systems of pain (7)(8) . This interaction between neural structures impairs the speed with which information reaches the brain and the processing capacity of this information, predisposing patients with chronic pain to cognitive deficit (7)(8) .…”
Section: Introductionmentioning
confidence: 99%
“…From the results, the authors considered that there are strong signs that pain harms/affects cognitive domains, evidencing the superposition of neuroanatomic and neurochemical substrates involved in pain and cognition (8) .…”
Section: Introductionmentioning
confidence: 99%